Hydrogen storage by spillover on Ni4 cluster embedded in three vacancy graphene. A DFT and dynamics study. (August 2022) - Ambrusi, R.E.; Orazi, V.; Marchetti, J.M.; Juan, A.; Pronsato, M.E.
Abstract: An ab initio dynamics study was performed with the aim of understanding better the hydrogen adsorption mechanism, stability and capacity with the temperature on Ni4 cluster embedded in a three vacancy graphene substrate. Additionally, the hydrogen migration to the substrate was analyzed observing an outstanding improvement for the activation energy compared with the systems without vacancies. Moreover, a suitable reduction in the hydrogen migration energy barriers was achieved with the subsequent hydrogen adsorption of more molecules on the cluster. Consequently, in the light of these new insights hydrogen spillover on Ni4 can be highly influenced by both, vacancy defects and the saturation with hydrogen molecules. Graphical abstract: Image 1 Highlights: Hydrogen adsorption on Ni4 embedded in three vacancy defected graphene is studied. AIMD and NEB calculations were performed. Adsorbed hydrogen stability with temperature on a Ni4 cluster is analyzed. Defect effect on the energy barrier reduction for H migration process is showed. The favoring of H spillover by Ni cluster H2 saturation was determined.